Cholinergic Signaling Attenuates Pro-Inflammatory Interleukin-8 Response in Colonic Epithelial Cells - Müller, Isabelle; Kym, Urs; Galati, Virginie; Tharakan, Sasha; Subotic, Ulrike; Krebs, Thomas; Stathopoulos, Eleuthere; Schmittenbecher, Peter; Cholewa, Dietmar; Romero, Philipp; Reingruber, Bertram; , NIGStudy Group; et al. (Frontiers in Immunology, 2022)
Infants affected by Hirschsprung disease (HSCR), a neurodevelopmental congenital disorder, lack ganglia of the intrinsic enteric nervous system (aganglionosis) in a variable length of the colon, and are prone to developing severe Hirschsprung-associated enterocolitis (HAEC). HSCR patients typically show abnormal dense innervation of extrinsic cholinergic nerve fibers throughout the aganglionic rectosigmoid. Cholinergic signaling has been reported to reduce inflammatory response. Consequently, a sparse extrinsic cholinergic innervation in the mucosa of the rectosigmoid correlates with increased inflammatory immune cell frequencies and higher incidence of HAEC in HSCR patients. However, whether cholinergic signals influence the pro-inflammatory immune response of intestinal epithelial cells (IEC) is unknown. Here, we analyzed colonic IEC isolated from 43 HSCR patients with either a low or high mucosal cholinergic innervation density (fiber-low versus fiber-high) as well as from control tissue. Compared to fiber-high samples, IEC purified from fiber-low rectosigmoid expressed significantly higher levels of IL-8 but not TNF-α, IL-10, TGF-1, Muc-2 or tight junction proteins. IEC from fiber-low rectosigmoid showed higher IL-8 protein concentrations in cell lysates as well as prominent IL-8 immunoreactivity compared to IEC from fiber-high tissue. Using the human colonic IEC cell line SW480 we demonstrated that cholinergic signals suppress lipopolysaccharide-induced IL-8 secretion via the alpha 7 nicotinic acetylcholine receptor (a7nAChR). In conclusion, we showed for the first time that the presence of a dense mucosal cholinergic innervation is associated with decreased secretion of IEC-derived pro-inflammatory IL-8 in the rectosigmoid of HSCR patients likely dependent on a7nAChR activation. Owing to the association between IL-8 and enterocolitis-prone, fiber-low HSCR patients, targeted therapies against IL-8 might be a promising immunotherapy candidate for HAEC treatment.